cAMP Response Element-Binding Protein (CREB): A Possible Signaling Molecule Link in the Pathophysiology of Schizophrenia - Wang, Haitao; Xu, Jiangping; Lazarovici, Philip; Quirion, Remi; Zheng, Wenhua (Frontiers in Molecular Neuroscience, 2018)
Dopamine is a brain neurotransmitter involved in the pathology of schizophrenia. The dopamine hypothesis states that in schizophrenia dopaminergic signal transduction is hyperactive. cAMP-response element binding protein (CREB) is a transcription factor that is activated by various extracellular stimuli and regulates the expression of genes important in dopaminergic neurons. Dopamine affects the phosphorylation of CREB via G protein coupled receptors. Neurotrophins, such as brain derived growth factor (BDNF), are critical regulators during neurodevelopment and synaptic plasticity. CREB is one of the major regulators of neurotrophin responses since activated CREB binds to the promoter region of BDNF and regulate its transcription. Moreover, susceptibility genes associated with schizophrenia also target and stimulate the activity of CREB. Abnormalities of CREB expression is observed in the postmortem brain of subjects with schizophrenia, and two variants (-933T to C and -413G to A) were found only in schizophrenic patients. CREB was also involved in the therapy of animal models of schizophrenia. Collectively, these findings suggest a link between CREB and pathophysiology of schizophrenia. This review provides an overview of CREB structure, expression and biological functions in the brain, interaction with dopamine signaling, neurotrophins and susceptibility genes for schizophrenia. Animal models in which CREB function is modulated, by either overexpression of the protein, or knocked down through gene deletion/mutation implicating CREB in schizophrenia and antipsychotic drugs efficacy are also discussed. Targeting research and drug development on CREB could enable the development of antidepressant medications with fundamentally new mechanisms of action.